Development of computer based simulation model for erbium-doped fiber amplifier - Akhter, Mst. Fowzia (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The founding of Erbium-doped fiber amplifier (EDFA) created a new era in communication technology, since it has the ability to provide a broad and high optical gain within the optical communication bandwidth (1013 to 1016 Hz). To date, EDFA is one of the active research areas in the field of optical communication. Many researches on one-stage (single pass and double pass) EDFAs have been carried out with well-established mathematical models. Recently, researchers are seeking interest to work on multi-stage (triple pass, quadruple pass etc.) EDFAs to achieve higher gain and lower noise figure for long haul optical communication systems. Although some researches have been done on multi-stage EDFAs, no mathematical model is developed till now. In addition to that the current commercial simulators available in the market cannot be used to determine the number of Erbium ions concentration in energy level 1 (N1) and energy level 2 (N2), while these parameters play an important role to determine the optimum fiber length and pump power. This thesis comes out with mathematical models for designing all possible two-stage and three-stage EDFA configurations. The mathematical models are developed based on energy levels rate equations and relaxation method. The effect of amplified spontaneous emission (ASE) is also included while determining the overall gain and noise figure of multi-stage EDFAs. Furthermore, a simulation model incorporating one-stage, two-stage and three-stage EDFA is developed using Matlab graphical user interface (GUI). The interface of this simulation model is developed in such a way that based on the input variables (fiber length, signal power, loss factors etc.) given by a user, the performance parameters (gain and noise figure) are shown on the display. The characteristics of all possible one-stage, two-stage and three-stage EDFAs are analyzed with the variation of pump power and signal power using this proposed simulation model. The optimum design parameters (pump power, signal power, fiber length) are also determined for specific input variables. The results obtained from this simulation model are compared against experimental data in order to validate the proposed model and the results are found equivalent to practical.